2006
DOI: 10.1128/aem.00122-06
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification ofRickettsia massiliaefromRhipicephalus sanguineusTicks Collected in Arizona

Abstract: Twenty Rhipicephalus sanguineus ticks collected in eastern Arizona were tested by PCR assay to establish their infection rate with spotted fever group rickettsiae. With a nested PCR assay which detects a fragment of the Rickettsia genus-specific 17-kDa antigen gene (htrA), five ticks (25%) were found to contain rickettsial DNA. One rickettsial isolate was obtained from these ticks by inoculating a suspension of a triturated tick into monolayers of Vero E6 monkey kidney cells and XTC-2 clawed toad cells, and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
111
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 63 publications
3
111
0
8
Order By: Relevance
“…364D. [31][32][33][34][35][36][37][38] There is also evidence that Rickettsia amblyommii , a tick-borne spotted fever group Rickettsia previously considered nonpathogenic, may cause mild illness and be misdiagnosed as RMSF on common serologic assays. 39 Geographic variations in severity have been noted, and a focus of unusually mild illness has been noted in North Carolina where R. amblyommii is prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…364D. [31][32][33][34][35][36][37][38] There is also evidence that Rickettsia amblyommii , a tick-borne spotted fever group Rickettsia previously considered nonpathogenic, may cause mild illness and be misdiagnosed as RMSF on common serologic assays. 39 Geographic variations in severity have been noted, and a focus of unusually mild illness has been noted in North Carolina where R. amblyommii is prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings expand the known geographic range in North America for R. massiliae , which now includes southern California in addition to a reported focus in Arizona. 5 Numerous ticks containing R. massiliae were present on this property during 2008-2009. Canine infection with R. conorii (the etiologic agent of Mediterranean spotted fever) shows clinical symptoms and serum and hematologic abnormalities similar to those of Rocky Mountain spotted fever. 34 In both infections, rickettsiemia detectable between days 2 and 12 after inoculation develops in acutely ill dogs.…”
Section: Discussionmentioning
confidence: 99%
“…conorii (the etiologic agent of Mediterranean spotted fever) is not resistant. 4,5,23 The similar clinical manifestations, common vector within the area endemic for Mediterranean spotted fever, and primary use of cross-reactive serologic assays for diagnosis of rickettsial diseases complicate understanding the true prevalence and distribution of R. massiliae and associated human or potentially canine infections. A limited canine serosurvey in northeastern Spain demonstrated that 8.6-25% (n = 93) of Catalonian dogs were exposed to R. massiliae Bar29 and 4-20% to R. conorii or another cross-reacting Rickettsia .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rickettsia prowazekii (the agent of epidemic typhus) was reported in A. cajennense or Amblyomma imitator ticks in Mexico (28). Interestingly, all of these Rickettsia species (except for "Candidatus Rickettsia andeanae") have been isolated in the United States, from the same tick species and/or from tick species different from those in Latin America (12,23,28,34,45).…”
mentioning
confidence: 99%